Traditional Food Identification In Kubung District, Solok District - Astuti, Silvia Sri; Kasmita, Kasmita; Yuliana, Yuliana; Gusnita, Wiwik; Mustika, Sari (Universitas Negeri Padang, 2023)
This research aims to learn deeper knowledge about traditional food products in Kec Kubung, Solok Regency. The research was carried out in October-December 2022 in the Kubung District, Solok Regency. To prevent the loss of these traditional foods, efforts are needed to preserve and introduce traditional food products to the current generation. The purpose of this research is to identify the types of food, materials used, and learn how to make traditional food. The type of research used is a mix method (qualitative and quantitative). Research data obtained from two ways, namely primary data and secondary data. Where the primary data is by identifying the types of traditional food, the ingredients used, and the way of making traditional food in Kec Kubung, Kab Solok, while secondary data is in the form of regional demographics in Kec Kubung, Kab Solok. Data collection techniques are carried out by observation, interviews, and documentation. Data analysis in the field by reducing data, presenting data, concluding then verifying. The conclusion from the results of the study is that traditional food in Kec Kubung, Kab Solok, is food that has been around for a long time. The materials used are self-developed food ingredients. As well as the equipment used is daily cooking equipment but still has a characteristic, namely the stove which is arranged in a triangular shape using wood.